2012
DOI: 10.1051/0004-6361/201117893
|View full text |Cite
|
Sign up to set email alerts
|

Spin period evolution of GX 1+4

Abstract: Aims. We aim both to complement the existing data on the spin history of the peculiar accreting X-ray pulsar GX 1+4 with more past and current data from BeppoSAX, INTEGRAL, and Fermi and to interpret the evolution in the framework of accretion theory. Methods. We used source light curves obtained from BeppoSAX/WFC and INTEGRAL/ISGRI to derive pulse periods using an epoch-folding analysis. Fermi/GBM data were analysed by fitting a constant plus a Fourier expansion to background-subtracted rates, and maximizing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 73 publications
10
81
1
Order By: Relevance
“…The timescale t ∞ between two torque reversals varies from source to source. Some pulsars show numerous torque reversals with moderate spin period derivative (e.g., Vela X−1, Her X−1; Bildsten et al 1997), others show quasi-periodic torque reversals superimposed on a longterm spin-up trend (e.g., OAO 1657−415, Barnstedt et al 2008; EXO 2030+375, Fermi/GBM 6 ; SAX J2103.5+4545, Camero et al 2014), while others show steady spin-up or spin-down sporadically interrupted by a torque reversal (e.g., GX 1+4, González-Galán et al 2012;4U 16264U −67, Beri et al 20144U 1907+09, Inam et al 2009. It is interesting to compare, for each pulsar, t ∞ with Δt gl , the time needed to reach the critical rotational lag for depinning.…”
Section: Observabilitymentioning
confidence: 99%
“…The timescale t ∞ between two torque reversals varies from source to source. Some pulsars show numerous torque reversals with moderate spin period derivative (e.g., Vela X−1, Her X−1; Bildsten et al 1997), others show quasi-periodic torque reversals superimposed on a longterm spin-up trend (e.g., OAO 1657−415, Barnstedt et al 2008; EXO 2030+375, Fermi/GBM 6 ; SAX J2103.5+4545, Camero et al 2014), while others show steady spin-up or spin-down sporadically interrupted by a torque reversal (e.g., GX 1+4, González-Galán et al 2012;4U 16264U −67, Beri et al 20144U 1907+09, Inam et al 2009. It is interesting to compare, for each pulsar, t ∞ with Δt gl , the time needed to reach the critical rotational lag for depinning.…”
Section: Observabilitymentioning
confidence: 99%
“…Its peculiar spin history has been the object of intensive study (Nagase 1989), and Makishima et al (1988) have shown a clear transition from spin-up to spin-down behavior in the equilibrium period, characterizing a torque-reversal episode. More recent studies (González-Galán et al 2012) have used data from BeppoSAX, INTEGRAL, Fermi and Swift/BAT to show that the source continues its spin-down trend with a constant change in frequency, and the pulse period has increased by ∼50% over the past three decades. Since the source is highly variable, our spectral and timing observations can possibly contribute to the flux and period histories for this peculiar object.…”
Section: Scientific Objectivesmentioning
confidence: 99%
“…The mask is made out of 1 mm-thick lead sheets and the basic cells are blue 20 mm × 20 mm squares. The pattern of closed and open elements are a cyclic extension (2 × 2) of a 13 × 13 Modified Uniformly Redundant Array (MURA) pattern (Gottesman & Fenimore 1989) with 20 mm-side square Fig. 4.…”
Section: The Coded Maskmentioning
confidence: 99%
See 2 more Smart Citations